Optimal load flow study - 182500 Siew, Ah Fong (Sekudai UTM, 1990)
In a power system, load flow analysis is used to study the steady state of the system. The analysis will indicata the status of teh system in terms of voltage, angle, active and reactive power flows in the individual transmission units, losses and reactive power generated or absorbed at voltage control buses. These ingormations will be used for system planning, operational planning and control. There are various solution methods and a careful analysis of the comparative merits and demerits of these methods in such respects as computer storage requirements, computational speed and convergence charactristics should be undertaken before a choice is made. This project is based on an existing fast decoupled load flow program that also incorporates sparsity and optimal ordering techniques. The program has been modified to run on-line for unit commitment. In addition to that, a database management facility has also been incorporated into the program for the convenience of the user. This modified program has also been tested out on different sets of standard IEEE busbar system and the result are found to be satisfactory.